Tobacco use and mental health : a policy brief (World Health Organization, Regional Office for Europe, 2020)
This policy briefing focuses on the interplay between mental health conditions and tobacco use. It reviews the evidence behind tobacco control interventions targeting people with mental health conditions and explains why they should be implemented. The suggested key policy recommendations to reduce smoking prevalence in people with mental health conditions include ensuring completely smoke-free health services, targeting mental health professionals through awareness campaigns and investing in tobacco cessation tailored to individuals with mental health conditions.
Keywords: poruchy vyvolané užíváním tabáku; Tobacco Use Cessation; duševní zdraví; Tobacco Use; veřejné zdravotnictví; ukončení užívání tabáku; psychiatrie; zdravotnické služby; Tobacco Use Disorder; Mental Health; Health Services; užívání tabáku